Different Paths to the Nation - Cole, Laurence. author. aut Link
XVI, 240 p.
Keywords: The essays in this volume analyse issues of national and regional identity during a key phase of nation-state formation in mid-nineteenth century Europe. By asking how contemporaries articulated regional and national identities, the book offers a fresh prospective on the process of nationalization in modern German, Austrian and Italian histories.